A lysine-based 2:1-[α/aza]-pseudopeptide series used as additives in polymeric membranes for CO2 capture: synthesis, structural studies, and application. Issue 15 (29th March 2023) - Ibrahim, Mohamed I. A.; Solimando, Xavier; Stefan, Loïc; Pickaert, Guillaume; Babin, Jérôme; Arnal-Herault, Carole; Roizard, Denis; Jonquières, Anne; Bodiguel, Jacques; Averlant-Petit, Marie-Christine
Abstract : A new 2:1-[α/aza]-pseudopeptide series based charged lysine amino acid was synthesized. Influences of chirality, backbone length, and lysine side chains on the oligomers conformation were investigated in solution using NMR, FTIR and MD calculations. Abstract : The current study presents for the first time the synthesis of a new 2:1-[α/aza]-pseudopeptide series possessing charged amino acids ( i.e., lysine) and aims at studying the influences of chirality, backbone length, and the nature of the lysine side chains on the conformation of the 2:1-[α/aza]-oligomers in solution using NMR, FTIR spectroscopy and molecular dynamic calculations. The spectroscopic results emphasized the conservation of the β-turn conformation adopted by the trimers regardless of the chirality which demonstrated a noticeable effect on the conformation of homochiral hexamer (8c ) compared with the hetero-analogue (8d ). The molecular dynamic calculations predicted that the chirality and the side chain of the lysine residues caused a little distortion from the classical β-turn conformation in the case of short trimer sequences (7c and 7d ), while the chirality and the backbone length exerted more distortion on the β-turn adopted by the longer hexamer sequences (8c and 8d ). The large disturbance in hexamers from classical β-turn was attributed to increasing the flexibility and the possibility of molecules to adopt a more energetically favorable conformation stabilized by non-classical β-turn intramolecular hydrogen bonds. Thus, alternating d - and l -lysine amino acids in the 2:1-[α/aza]-hexamer (8d ) decreases the high steric hindrance between the lysine side chains, as in the homo analogue (8c ), and the distortion is less recognized. Finally, short sequences of aza-pseudopeptides containing lysine residues improve CO2 separation when used as additives in Pebax® 1074 membranes. The best membrane performances were obtained with a pseudopeptidic dimer as an additive (6b′ ; deprotected lysine side chain), with an increase in both ideal selectivity α CO2 /N2 (from 42.8 to 47.6) and CO2 permeability (from 132 to 148 Barrer) compared to the virgin Pebax® 1074 membrane.